Diagnosis and treatment of acute phlegmonous gastritis: A case report. Issue 18 (May 2018) - Yang, Hongxin; Yan, Zhiqiang; Chen, Jiaju; Xie, Haitao; Wang, Haibin; Wang, Qian
Abstract: Rationale: Acute phlegmonous gastritis (PG) is a rare and often fatal condition mainly characterized by severe bacterial infection of the gastric wall. Case reports of PG over the past century average about 1 per year. Early diagnosis and immediate treatment are crucial to achieve positive outcomes. Patient concerns: A 47-year-old man was referred to our hospital because of abdominal pain, high fever, and vomiting for 4 days, with aggravation for 24 hours. Physical examination revealed epigastric abdominal pain, rebound pain, and abdominal wall tightness. Abdominal CT showed thickening of the stomach wall with edema and gas. Diagnoses: On the basis of symptoms and CT imaging findings, the patient was diagnosed with acute PG. Interventions: Antibiotic therapy and operation. Outcomes: The patient immediately underwent an operation after conservative treatment using antibiotics proved ineffective. The whole stomach was obviously swollen, and the anterior side and posterior wall of the stomach were nigrescent necrotic. Hence, total gastrectomy was performed followed by reconstruction (roux-en-y), and pus that accumulated in the stomach wall was cultured. At postoperative broad-spectrum antibiotic coverage, the patient finally recovered. Lessons: Acute PG is a rare infection of the gastric wall especially after antibiotic treatment. Given the fast progression of this disease, early recognition and immediate action are crucial to achieve positive outcomes.